Antibacterial Activity of Traditional Medicinal Plants Used for the Treatment of Acute Diarrheal Diseases in Chiapas, Mexico - Jesús Mauricio Ernesto Hernández-Méndez; Israel Peña-Hernández; Mariela Tapia-Nazario; Gerardo Leyva-Padrón; Abumalé Cruz-Salomón; María Emperatriz Domínguez-Espinosa; Héctor Armando Esquinca-Avilés; Maritza del Carmen Hernández-Cruz; Rocío Magdalena Sánchez-Albores; Kelly del Carmen Cruz-Salomón; Rosa Isela Cruz-Rodríguez; Martha Guadalupe Gómez-Santos (Microbiology Research)
The Enterobacteriaceae family poses health risks due to its role in gastrointestinal diseases like acute diarrhea. With rising antibiotic resistance, plants offer promising antibacterial compounds with low toxicity. This study evaluated the antibacterial activity, minimum inhibitory concentration (MIC), and toxicity of ethanolic (EE) and aqueous (AE) extracts from five Mexican medicinal plants traditionally used in Chiapas for treating acute diarrheal diseases (ADD). Antibacterial activity was assessed using disk diffusion assays and MIC determined by macrodilution. Toxicity tests were performed using Artemia salina. As a result, EE extracts exhibited higher antibacterial activity than AE extracts. Byrsonima crassifolia effectively inhibited Salmonella enteritidis (78.26%, MIC 50 mg/mL) and Shigella dysenteriae (76.19%, MIC 25 mg/mL). Solanum torvum showed efficacy against Escherichia coli (55.55%, MIC 12.5 mg/mL) and Salmonella enteritidis (73.91%, MIC 25 mg/mL). Euphorbia maculata inhibited Shigella dysenteriae (104.76%, MIC 25 mg/mL), while Guazuma ulmifolia and Bursera simaruba exhibited no antibacterial effects. All extracts were non-toxic (LD50 > 1000 μg/mL), indicating potential as natural alternatives for ADD treatment.